Factor of combined pathology in geriatric patients with prostate adenoma - I. G. Leshchenko; A. I. Akimov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Samara Regional Clinical Hospital of War Veterans in the period from 2000 to 2015 examined and treated 639 elderly and senile patients with prostate adenoma, who underwent an isolated adenomectomy, transurethral prostate resection, or simultaneous surgery. Among them, 191 (29.9%) patients underwent simultanous surgery. The paper presents the nature and frequency of dominant concomitant diseases in geriatric patients with prostate adenoma in the first (2000-2006) and second (2007-2015) periods of the study. Application in the second period of the author's therapeutic and diagnostic developments, taking into account concomitant pathology, significantly affected the reduction of a number of severe intra- and postoperative complications and lethality in comparison with the first period.